2006
DOI: 10.1002/tox.20212
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced changes in pigments, total phenolics, and phenylalanine ammonia-lyase activity in fronds ofAzolla imbricata

Abstract: This study was designed to examine the effects of cadmium on several color-related parameters (including chlorophyll, carotenoid, and anthocyanin), total phenolics, and phenylalanine ammonia-lyase (PAL) activity in an aquatic fern species Azolla imbricate (A. imbricata). Cd accumulation and effects in the fronds were closely related with Cd concentration in the growth medium. The fronds under 0.5 mg/L Cd treatment turned red on the 3rd day, and this color change also appeared under 0.05 and 0.1 mg/L Cd treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 52 publications
3
57
0
1
Order By: Relevance
“…In line with our results, Ali et al (2006) observed higher PAL activity and total phenols in root suspension cultures of Panax ginseng, comparing 40th and 20th days of exposure to Cu doses up to 50 lM. In fronds of the fern Azolla imbricata, Dai et al (2006) observed that Cd at a dose of 4.45 lM increased PAL activity up to the 5th day of exposure, but then it decreased up to the 9th day of exposure. This finding could support our hypothesis on the different time dynamics of PAL activity under Cd and Cu excess.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In line with our results, Ali et al (2006) observed higher PAL activity and total phenols in root suspension cultures of Panax ginseng, comparing 40th and 20th days of exposure to Cu doses up to 50 lM. In fronds of the fern Azolla imbricata, Dai et al (2006) observed that Cd at a dose of 4.45 lM increased PAL activity up to the 5th day of exposure, but then it decreased up to the 9th day of exposure. This finding could support our hypothesis on the different time dynamics of PAL activity under Cd and Cu excess.…”
Section: Discussionsupporting
confidence: 87%
“…Its enhanced activity could therefore be assumed in stressed plant tissue. Recently, Ali et al (2006) recorded a stimulatory effect of Cu on PAL in Panax ginseng and the influence of Cd on PAL activity has been studied in fronds of Azolla imbricata (Dai et al, 2006). Notwithstanding, data related to cadmium effect on PAL activity under Cd stress and the comparison of metals with different redox properties is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The Pb content was 0.37, 2.3, and 1.8% of the dry weight after 2, 4, and 6 days of growth, respectively, in the whole plant, while the isolated Azolla apoplast contained 0.125, 1.22, and 1.4% Pb, respectively. Sela et al (1989) reported that A. filiculoides also accumulate heavy metals such as Cd, Cr, Cu, and Zn and their content was 10,000, 1990, 9000, A. imbricata Cd 0.5 lg l -1 9 183 lg Cd g -1 Dai et al (2006) and 6500 ppm, respectively (Table 4). Arora et al (2004Arora et al ( , 2006 (Bennicelli et al 2004).…”
Section: Phytoremediation Ability Of Azollamentioning
confidence: 99%
“…The bioaccumulation of heavy metals by Azolla spp. is known to exhibit a concentration-dependent relationship (Stepniewska et al 2005;Arora et al 2006;Dai et al 2006;Rai and Tripathi 2009). Duncan (1997, 1998a, b) investigated the removal of sexivalent Cr, Ni, and Zn by A. filiculoides from aqueous solution and from electroplating rinse effluent.…”
Section: Biosorption Of Heavy Metals By Azollamentioning
confidence: 99%
See 1 more Smart Citation